Efficacy of Integrated Social Cognitive Remediation vs. Neurocognitive Remediation in Improving Functional Outcome in Schizophrenia: Concept and Design of a Multicenter, Single-Blind RCT (The ISST Study) - Wölwer, Wolfgang; Frommann, Nicole; Lowe, Agnes; Kamp, Daniel; Weide, Karolin; Bechdolf, Andreas; Brockhaus-Dumke, Anke; Hurlemann, Rene; Muthesius, Ana; Klingberg, Stefan; Hellmich, Martin; Schmied, Sabine; et al. (Frontiers in Psychiatry, 2022)
Background Although clinically effective treatment is available for schizophrenia, recovery often is still hampered by persistent poor psychosocial functioning, which in turn is limited by impairments in neurocognition, social cognition, and social behavioral skills. Although cognitive remediation has shown general efficacy in improving cognition and social functioning, effects still need to be improved and replicated in appropriately powered, methodologically rigorous randomized controlled trials (RCTs). Existing evidence indicates that effects can most likely be optimized by combining treatment approaches to simultaneously address both social cognitive and social behavioral processes. Objectives To assess whether Integrated Social Cognitive and Behavioral Skill Therapy (ISST) is more efficacious in improving functional outcome in schizophrenia than the active control treatment Neurocognitive Remediation Therapy (NCRT). Methods The present study is a multicenter, prospective, rater-blinded, two-arm RCT being conducted at six academic study sites in Germany. A sample of 180 at least partly remitted patients with schizophrenia are randomly assigned to either ISST or NCRT. ISST is a compensatory, strategy-based program that targets social cognitive processes and social behavioral skills. NCRT comprises mainly drill and practice-oriented neurocognitive training. Both treatments consist of 18 sessions over 6 months, and participants are subsequently followed up for another 6 months. The primary outcome is all-cause discontinuation over the 12-month study period; psychosocial functioning, quality of life, neurocognitive and social cognitive performance, and clinical symptoms are assessed as secondary outcomes at baseline before randomization (V1), at the end of the six-month treatment period (V6), and at the six-month follow-up (V12). Discussion This RCT is part of the German Enhancing Schizophrenia Prevention and Recovery through Innovative Treatments (ESPRIT) research network, which aims at using innovative treatments to enhance prevention and recovery in patients with schizophrenia. Because this study is one of the largest and methodologically most rigorous RCTs on the efficacy of cognitive remediation approaches in schizophrenia, it will not only help to identify the optimal treatment options for improving psychosocial functioning and thus recovery in patients but also allow conclusions to be drawn about factors influencing and mediating the effects of cognitive remediation in these patients. Trial Registration ClinicalTrials.gov NCT 02678858, German Study Register DRKS 00010033